2017
DOI: 10.1016/j.jvs.2017.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Lower extremity bypass for critical limb ischemia decreases major adverse limb events with equivalent cardiac risk compared with endovascular intervention

Abstract: Objective Lower extremity bypass (LEB) has traditionally been the gold standard in the treatment of critical limb ischemia (CLI). Infrainguinal endovascular intervention (IEI) has become more commonly performed than LEB but comparative outcomes are limited. We sought to compare rates of Major Adverse Limb Events (MALE) and Major Adverse Cardiovascular Events (MACE) after LEB and EI in a propensity score matched, national cohort of patients with CLI. Methods The National Surgical Quality Improvement Program (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…Further research is required to determine if the CS data reported here are generalizable to current vascular surgical practice and, if so, to determine the reasons for these unexpected data. Possible causes include a loss of surgical skills as a result of the overall reduction in open vascular procedures and/or a tendency to reserve BS for patients considered unsuitable for endovascular intervention due the severity of their tissue loss and/or the extent and complexity of their underlying disease [12][13][14][15] . While loss of surgical skills is certainly possible, this does not appear to be supported by the observation that CS patients had lower overall 30-day mortality and morbidity as well as a trend towards a shorter index admission [16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to determine if the CS data reported here are generalizable to current vascular surgical practice and, if so, to determine the reasons for these unexpected data. Possible causes include a loss of surgical skills as a result of the overall reduction in open vascular procedures and/or a tendency to reserve BS for patients considered unsuitable for endovascular intervention due the severity of their tissue loss and/or the extent and complexity of their underlying disease [12][13][14][15] . While loss of surgical skills is certainly possible, this does not appear to be supported by the observation that CS patients had lower overall 30-day mortality and morbidity as well as a trend towards a shorter index admission [16][17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…A propensity-matched cohort study by Mehaffey et al 3 ) investigated lower extremity bypass (LEBs) versus endovascular intervention (IEIs) among 13,294 LEBs and IEIs with 8,066 cases performed for CLI. There was a significantly lower risk-adjusted 30-day MALE rate compared with IEI, with significant reduction in amputation rates.…”
Section: Appraisal Of Aha/acc Guideline Statements and The Appadc Recmentioning
confidence: 99%
“…Several studies of PAD have shown open bypass patients have reduced risk of MALE when compared to those who undergo endovascular revascularizations, though these studies often include only CLI patients. 12-14 Currently there is no high quality data regarding 30-day outcomes after revascularizations for claudicants, particularly utilizing the OPG definitions of MALE. However, a study by Siracuse et al compared longer-term outcomes after LEB and IEI in those with superficial femoral artery (SFA) disease.…”
Section: Discussionmentioning
confidence: 99%